2015
DOI: 10.31018/jans.v7i2.707
|View full text |Cite
|
Sign up to set email alerts
|

Economic loss assessment on juvenile fish catch due to forced non-selectivity in a selective fishing gear, gillnet along Mumbai coast, India

Abstract: Abstract:A study on quantity and value of juvenile fish landings was carried out in the gillnet fishery of three selected landing centers along Mumbai coast viz., Versova, Cuff Parade and Mahim in India using Out board motors (OBM), Inboard motors (IBM) and non-motorised gillnetters respectively. The data on the quantity and value of landed juveniles were collected and analysed to reach a consensus on the gross economic loss on account of juvenile fishing. A bio-economic model was used to estimate economic los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Tsikliras and Polymeros' (2014) findings showed that larger fishes were consistently attaining higher market value than their small and medium counterparts. In a study conducted by Dar et al (2015), the capture of juvenile fish elicited enormous economic loss in selected landing centers in India. Zimmerman and Heino (2013) accentuated that change in catch composition greatly influences size-dependent pricing.…”
Section: Overall Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsikliras and Polymeros' (2014) findings showed that larger fishes were consistently attaining higher market value than their small and medium counterparts. In a study conducted by Dar et al (2015), the capture of juvenile fish elicited enormous economic loss in selected landing centers in India. Zimmerman and Heino (2013) accentuated that change in catch composition greatly influences size-dependent pricing.…”
Section: Overall Lossmentioning
confidence: 99%
“…Growth overfishing occurs when there is massive removal of immature fish, which impedes the ability of fish stocks to replenish themselves. It is regarded as detrimental because it may further aggravate the current problem of resource depletion (Green et al 2003;Kamei et al 2013;Dar et al 2015). Moreover, the capture of fish below its marketable size induces a potential loss of revenue due to its lower market value.…”
Section: Introductionmentioning
confidence: 99%